Rancang Bangun Perangkat Lunak Pemesanan Jasa Seni Dengan Metode Extreme Programming - sari, Mirga krisma nilam; kurniati, Rezki; Subandri, M Asep (Universitas Islam Syekh Yusuf, 2021)
Indonesia is an archipelagic country that stretches from Sabang to Merauke, making Indonesia rich in ethnicity, language, culture and art. Each region in Indonesia has its own characteristics and uniqueness, one of which can be seen from the traditional music that is owned. Traditional music is an instrument that can produce sound and is played by the surrounding community which serves to entertain and is used for traditional ceremonies. Previously there were problems in ordering art services, namely with manual promotion and marketing such as using brochures, word of mouth and social media. Customers who want to order art services must come directly to the music owner's place to process the art order by telephone. Usually, negotiations will be carried out when they want to pay for services. Payment is made after the event is over. Due to the absence of an online art service ordering system. So that many customers have difficulty ordering time for art services. Expected information This system will make it easier for customers to obtain information. As a solution to the problems above, the author builds a